2013
DOI: 10.1166/jnn.2013.6847
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Antioxidative and Antiapoptotic Genes Expression in irradiated K562 Cells Upon Fullerenol C<SUB>60</SUB>(OH)<SUB>24</SUB> Nanoparticle Treatment

Abstract: Recent data established the prospective applications for fullerenol (C60(OH)24) nanoparticle (FNP) in many fields, such as antioxidants, neuroprotective agents, and potential anti-radiation drugs. Leukemia cell sensitization to apoptosis induced by ionizing radiation is achieved by upregulation of ROS production and/or downregulation of antioxidative enzymes. Therefore, our aim was to analyze the potential role of fullerenol nanoparticle in modulation of the leukemic cellular response to irradiation. We used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…[14][15][16][17] Polyhydroxylated fullerenes, also known as fullerols [C 60 (OH) n ], belong to a group of antioxidant nanoparticles that exhibit strong antioxidant activity in both in vitro and in vivo biological systems. 13 It has been demonstrated that the anti-inflammatory, 18 antiapoptotic, 16,17 radioprotective, 19,20 and neuroprotective effects 21,22 and the enzyme-inhibitory activity of fullerols 13 have been attributed to their ability to scavenge free radicals, such as superoxide anion radical, hydroxy radical, and nitrous oxide radical. It has since been well established that induction of Nrf2-regulated phase II antioxidant enzymes by nutritional or pharmacological intervention is an effective approach to combat the toxicities of ROS and to protect cells against oxidative stress.…”
Section: Ye Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] Polyhydroxylated fullerenes, also known as fullerols [C 60 (OH) n ], belong to a group of antioxidant nanoparticles that exhibit strong antioxidant activity in both in vitro and in vivo biological systems. 13 It has been demonstrated that the anti-inflammatory, 18 antiapoptotic, 16,17 radioprotective, 19,20 and neuroprotective effects 21,22 and the enzyme-inhibitory activity of fullerols 13 have been attributed to their ability to scavenge free radicals, such as superoxide anion radical, hydroxy radical, and nitrous oxide radical. It has since been well established that induction of Nrf2-regulated phase II antioxidant enzymes by nutritional or pharmacological intervention is an effective approach to combat the toxicities of ROS and to protect cells against oxidative stress.…”
Section: Ye Et Almentioning
confidence: 99%
“…In an animal irradiated model that is associated with oxidative stress, pretreatment with C 60 (OH) 24 showed radioprotective effects by scavenging ROS and increasing the antioxidant enzyme activities. 19,20 It has also been reported that C 60 (OH) 24 shows hepatoprotective effects in doxorubicin-treated rats by acting as an antioxidant. 44,45 Hence, it is possible to propose that C 60 (OH) 24 pretreatment prevented deleterious effects of ROS by direct ROS scavenging or increasing the antioxidant enzyme activities.…”
mentioning
confidence: 96%
“…But the expression of anti-apoptotic and cytoprotective genes was modulated. Similarly, most of the cytoprotective genes were elevated with the pre-treated C60(OH)24, such as CAT, Mn-SOD, nitric oxide synthase, glutathione Stransferase isoform GSTA4, glutathione peroxidase and gamma-glutamyltransferase [40].…”
Section: Radical Scavenger: Protect Cells From the Radiationmentioning
confidence: 95%
“…Recent research, investigating the role of fullerenol C 60 (OH) 24 in modulation of the response of K562 leukemic cells to irradiation, indicated that fullerenol improved survival of the irradiated cells and produced significant overexpression of antiapoptotic Bcl-2 and Bcl-xL proteins as well as cytoprotective GSTA4, MnSOD, NOS, CAT, and HO-1 genes [39]. …”
Section: Potential Application Of Fullerenols In Radiobiologymentioning
confidence: 99%